Metallography Evaluation of IN 718 after Applied Heat Treatment - Belan, Juraj; Hurtalová, Lenka; Vaško, Alan; Tillová, Eva (Manufacturing Technology Journal, 2014)
INCONEL alloy 718 is a high-strength; corrosion-resistant nickel chromium alloy used at -253 °C to 705 °C for production of heat resistant parts of aero jet engine mostly. Mechanical properties of this alloy is strongly depended on microstructure and from presence of structural features such are gamma double prime (), gamma prime () and delta (δ) phases. Mentioned phases precipitate at various temperature ranges and Nb content as well. Article deals with applying of heat treatment at 800°C for 72 hours and its influence on structure changes. For microstructure evaluation a techniques of scanning electron microscopy (SEM) were used.
Keywords: Inconel alloy 718; Gamma double prime and Gamma prime precipitation; Heat treatment or Re-heating of alloy; Microstructure evaluation